Human capital, growth and convergence traps: Implications from a cross-country analysis - P.E. Petrakis; D. Stamatakis (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
This article, adapted from Tamura?s theoretical proposition, empirically investigates capital convergence in three country groups belonging to significantly different development categories: G7, developed and developing. Human capital evaluation, in this context, goes beyond enrolment and/or attainment rates. In addition to enrolments and government spending, alternative factors determining human capital effectiveness synthesize an idea of enhanced human capital proxy. Empirical results indicate moderate evidence of convergence among the three-country groups when conventional variables are included. The convergence ?picture? is quite different when additional variables are empirically examined, implying the existence of a ?convergence trap? caused by initial endowments on human capital.
Keywords: 330; advanced (OECD); developed (OECD); developing (world); USA; Mexico; Mauritius (as examples of each of the above); human capital; convergence